Modeling the effect of static stretching and strengthening exercise in lengthened position on balance in low back pain subject with shortened hamstring: a randomized controlled clinical trial - Shamsi, MohammadBagher (BMC Musculoskelet Disord, 2020)
BACKGROUND: Hamstring shortening may have negative impacts on function and biomechanics of knee and hip joints and lumbo-pelvic rhythm. Many interventions are believed to correct hamstring to its normal length. There are several reports of impairment in postural control of patients with low back pain. The purpose of this study was to compare the effect of stretching exercise and strengthening exercise in lengthened position of the hamstring muscle on improving the dynamic balance of the person in patients with chronic low back pain with short hamstring muscles. METHODS: Forty-five patients with hamstring shortening who referred to physiotherapy clinic of Kermanshah university of Medical Sciences, Kermanshah, Iran were randomly allocated to the three groups; static stretching (n = 15), strengthening exercise in lengthened hamstring position (n = 15) and control (n = 15). All groups received conventional physiotherapy for low back pain and the two intervention groups received stretching exercise and strengthening exercise in lengthened position programs as well. All groups performed three treatment sessions for a week, a total of 12 sessions. For balance assessment, Y-Balance test was performed for each participant in three reach directions. To determine the important and significant variables, all variables entered a model (Generalized Estimation Equations method). RESULTS: The results indicate that based on GEE model, by controlling other variables, participants of static stretching exercise showed more improvement in balance than control group (β = 9.58, p-value = 0.014). Also, balance status showed significant improvement in the end of study compared to baseline of the study (β = 7.71, P-value< 0.001). In addition, the balance in three reach directions improved significantly and the greatest balance improvement was in the anterior reach direction (β ranged over = 6.16 to 11.59) and the height of patients affected their balance (β = 0.28, P-value = 0.034). CONCLUSIONS: Group (type of intervention), phase of intervention, reach direction of test (anterior, posteromedial and posterolateral) and height of participants were associated with balance performance. Static stretching exercise was more effective than muscle strengthening exercise in lengthened position for improving dynamic balance in low back pain patients with hamstring tightness. TRIAL REGISTRATION: Iranian Registry of Clinical Trials (IRCT201507258035n2). Registered 16th September 2015.